PERFORMANCE MANAGEMENT PRACTICE IN THE WORKPLACE: A Qualitative Studies Based on Comparative Model Theories and Literature Reviews - Bunteng, Long (Srawung: Journal of Social Sciences and Humanities, 2025)
Performance management is among the research topics that has been continuously studied throughout the global academic institutions. It is the major area of concerns by both public and private organizations since it entirely linked to the organizational productivities and the expected standard goals. Performance management is tied to the strategy of the organization leadership and has a strong impact on the entire organizational performance. In view of this, the purpose of this study is to identify relevant factors that promote the higher employee performance in different industries. In this literature study, factors such as job satisfaction, job commitment, and job engagement will be deeply reviewed and further proved if they are the key factors to enhance the job performance in an organization. The study is conducted using qualitative methods based on previous recent publications and reports by both public and private industries. In addition, three models of motivational theories such as equity, expectancy, and two-factor theory are employed in this study. The findings from these comparative studies from previous researches and corporate report show that the four factors have been found its alignment between each other. Job satisfaction leads to job commitment, job commitment leads to higher job engagement, and higher job engagement leads to higher employee performance. The absence of one factor will definitely lead to the absence of another.